2000
DOI: 10.1046/j.1365-2672.2000.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an arylesterase from Lactobacillus helveticus CNRZ32

Abstract: An esterase gene (estA) was isolated from a previously constructed genomic library of Lactobacillus helveticus CNRZ32. The estA gene consisted of a 558 bp open reading frame encoding a putative peptide of 21·3 kDa. Protein sequence homology searches using BLAST revealed that EstA had low amino acid sequence identity with the serine‐dependent arylesterases TesI (24%) and EtpA (26%) from Escherichia coli and Vibrio mimicus, respectively. A recombinant EstA fusion protein containing a C‐terminal six‐histidine tag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 51 publications
6
66
0
2
Order By: Relevance
“…The gene estA encoding an esterase that can catalyze the biosynthesis of esters derived from short-chain fatty acids was cloned and characterized in lactococcal strains (28), as well as in Lactobacillus helveticus (26) and L. casei (74). These estA genes shared high sequence similarity and could be easily distinguished from other esterases (17,26; data not shown). Many LAB genomes, like those of the lactococci and streptococci, have one estA gene (Table 1).…”
Section: Enzymes Involved In the Transamination Routementioning
confidence: 99%
“…The gene estA encoding an esterase that can catalyze the biosynthesis of esters derived from short-chain fatty acids was cloned and characterized in lactococcal strains (28), as well as in Lactobacillus helveticus (26) and L. casei (74). These estA genes shared high sequence similarity and could be easily distinguished from other esterases (17,26; data not shown). Many LAB genomes, like those of the lactococci and streptococci, have one estA gene (Table 1).…”
Section: Enzymes Involved In the Transamination Routementioning
confidence: 99%
“…The wild-type MVP1 GDGL motif was mutated to EDGL in the mvp1 mutant. The Ser residue contained in the GDSL motif is crucial for enzymatic activity (Akoh et al, 2004), and multiple site-directed mutagenesis studies of lipases/esterases from Aeromonas hydrophila (Hilton and Buckley, 1991), Lactobacillus helveticus (Fenster et al, 2000), and Vibrio mimicus (Shaw et al, 1994) have demonstrated that mutagenesis of the Ser residue in the GDSL motif completely abolishes enzymatic activity. We found that MVP1 did in fact lack lipase activity.…”
Section: Cloning and Identification Of Mvp1 As A Myapmentioning
confidence: 99%
“…Most characterization of esterases in LAB has focused on dairy isolates (9,(16)(17)(18)20). Parallel work in a wine context is limited despite general acceptance of the importance of esters in wine.…”
mentioning
confidence: 99%